Prussian blue analogs: electrosynthesis and characterization - Lezna, Reynaldo Oscar (2003)
This article focuses on the electrodeposition and in situ characterization of Prussian blue analogs with the generic formula: AMk[Fe(CN)d i-mHf), where h, k, I, m are stoichiometric numbers, A = alkali metal cation, and M is a transitionmetal. Six such metal hexacyanoferrate (MHCF) compounds derived from Cu, Pd, In, V, Co and Ni are featured in this article. The electrodeposition of MHCF films on targeted substrates is discussed through data obtained by cyclic voltammetry and complementan’ techniques. In situ spectroelectrochemical characterization of these films in the infrared and UV-visible regions is then discussed and constitutes the main topic of this article.